Energy-efficient optimal algorithm based on uplink multi-user very large MIMO system - UYing H; IBao-feng J; UANGYong-ming H; UFei Y; ANGLV-xi Y (Tongxin xuebao)
Using the energy efficiency lower bound as the optimization criterion,a resource allocation algorithm was investigated under uplink multi-user very large MIMO systems.Specifically,both the number of antenna arrays at the BS and the transmit data rate at the user are adjusted to maximize the energy efficiency,in which the power consumption accounts for both transmit power and circuit power,meanwhile the BS uses a zero forcing(ZF) receiver.The existence of a unique globally optimal resource allocation solution was demonstrated by exploiting the properties of objective function.Furthermore,by transforming the originally fractional optimization problem into an equivalent subtractive form using the properties of fractional programming,an iterative resource allocation algorithm was developed to achieve the optimum was developed.Simulation results show that the algorithm converge to a near optimal solution only with a small number of iterations.